Apparent-weakening by adaptive passive stiffness shaping along the height of multistory building using negative stiffness devices and dampers for seismic protection. (1st October 2020) - Nagarajaiah, Satish; Sen, Debarshi
Highlights: Apparent weakening by adaptive stiffness shaping of structures using a negative stiffness device (NSD) for earthquake protection. In this numerical study, we propose and verify the concept of adaptive stiffness shaping of a nine-story yielding structure. Results presented confirm that the addition of NSD + NDs protects the structure from strong ground motion and improves performance. Based on the performance for eight strong ground motions, we conclude that NSDs in conjunction with nonlinear dampers provide the significant response reductions. We show that in addition to reduction of peak responses, the NSD systems in some cases also reduce the number of cycles of large base shears and deformations of the structure, hence aiding reducing fatigue damage to structures. Results show, that if the distribution of apparent yield is properly designed for a structure, NSDs with nonlinear dampers results in a superior performance compared to the other cases considered in this paper. Abstract: Apparent weakening by adaptive stiffness shaping of structures using a negative stiffness device (NSD) is a new passive structural control approach to mitigate the response of structures during severe ground motions. Experimental studies confirm significant reductions in acceleration, inter-story drift and base shear experienced by a structure when a NSD is deployed in conjunction with a viscous damper. So far, the focus and application of NSDs has been restricted to response reduction in the story where a NSD is installed and its effect on stories above that. In this paper, we demonstrate the efficacy of deploying NSDs accompanied by dampers at multiple locations along the height of an example nine story structure. Typically, the NSDs in the lower floors undergo large deformations since the energy from a ground motion is transmitted from the bottom to top. To prevent this, we propose a generalized scheme to incorporate NSDs at all floors with different apparent-yield displacements. We incorporate the variations with a view towards minimizing localized inter-story deformations (ISD) and distribute the effects of strong ground motions evenly along the height of the structure. In addition to the variation of apparent-yield of NSDs, we study the effects of supplementing the NSD with linear and non-linear dampers. We compare the response of the nine story structure without passive control devices (BS) to cases where linear dampers (LD) are attached, nonlinear dampers are attached (ND), NSDs in conjuction with linear dampers are attached (NSD + LD) and NSDs in conjunction with nonlinear dampers are attached (NSD + ND). Our results show that if the distribution of apparent yield is properly designed for a structure, NSDs with nonlinear dampers results in a superior performance compared to the other cases considered in this paper.